2020
DOI: 10.1016/j.stemcr.2019.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Pathways in Early-Onset Autosomal Recessive Parkinson's Disease Discovered Using Isogenic Human Dopaminergic Neurons

Abstract: Parkinson's disease (PD) is a complex and highly variable neurodegenerative disease. Familial PD is caused by mutations in several genes with diverse and mostly unknown functions. It is unclear how dysregulation of these genes results in the relatively selective death of nigral dopaminergic neurons (DNs). To address this question, we modeled PD by knocking out the PD genes PARKIN (PRKN), DJ-1 (PARK7), and ATP13A2 (PARK9) in independent isogenic human pluripotent stem cell (hPSC) lines. We found increased level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(73 citation statements)
references
References 39 publications
4
68
0
Order By: Relevance
“…PD is a complex disorder with heterogeneity in pathophysiology and clinical presentation. This is clearest in monogenic PD patients; for example Lewy bodies, a hallmark of PD pathology, are not seen in all PINK1, Parkin and LRRK2 associated PD patients (180)(181)(182). Mitochondrial or mitophagy defects may be involved to a different degree in different patients and at different times.…”
Section: Lack Of Significant Phenotype In Pink1 Ormentioning
confidence: 99%
“…PD is a complex disorder with heterogeneity in pathophysiology and clinical presentation. This is clearest in monogenic PD patients; for example Lewy bodies, a hallmark of PD pathology, are not seen in all PINK1, Parkin and LRRK2 associated PD patients (180)(181)(182). Mitochondrial or mitophagy defects may be involved to a different degree in different patients and at different times.…”
Section: Lack Of Significant Phenotype In Pink1 Ormentioning
confidence: 99%
“…More recent evolutions of these protocols have confirmed the initial observations, as well as aimed at increasing the quality and reproducibility of hMO ( 67 , 72 76 ) and better estimating their yield of mDA neurons. For instance, using a high content image analysis approach, Smits et al ( 73 ) showed that TH+ cells composed 62% of all cells after 1 month of differentiation, while Ahfeldt et al ( 74 ) found using a knock-in TH:tdtomato line, that TH+ cells composed ~38% of total cells at a similar timepoint. Such differences are likely to arise from cell line effects as well as protocol variations.…”
Section: Modeling Pd In Vitromentioning
confidence: 99%
“…More recently, an extensive report from Ahfeldt et al ( 74 ) used hMO to study the roles of 3 severe PD-associated mutations (in PRKN/PARK2, DJ1/PARK7 , and ATP13A2/PARK9 ) through genomic editing of a healthy control hiPSC line. RNAseq analyses of TH+ cells after 1 month of differentiation found that PRKN –/– mDA neurons showed the highest amount of differentially expressed genes (1641) compared to controls.…”
Section: Modeling Pd In Vitromentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, theoretical indices derived from DA/metabolites relative ratios have suggested that both reduced vesicular DA uptake and ALDH1A1 activity accounted for DOPAL accumulation in PD putamen ( Goldstein et al, 2013 ). Quantitative proteomics and transcriptomics highlighted mitochondrial and lysosomal dysregulation and differential vulnerability of DAergic neurons derived from several isogenic PD gene knockout pluripotent stem cell lines ( Ahfeldt et al, 2020 ).…”
Section: Alpha-synuclein and Major Determinants Of Pd Dopaminergic Vumentioning
confidence: 99%